(3QSGdI aj GdGSFdI hGdCLhHI GdWHjIs
(3ChdgG (B:s
(3SDGd bO PcQ GdTjN ai GdbGfhf MjK jJcde ai hbO jchf Hhd CMeQ jLQi ajg ShGO GdLhGH GdHhd GdCMeQ GdPi jLQi ajg ShGO ajOd Ydi GdMejGJ s
(3BNQgG (B:s
(3GdHGQO hGdjGHS hGdbGHV aJQO Ydi Jdc GdGYVGA hGdfGaP ajbHVgG hjHQOgG hjbhjgG Ydi GdEeJfGY Yf YhO eG SGd hGfUHGH eG PGH ef ehVY BNQ EdjgG JeJ GdGSFdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGOSI YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs